THE APPLICATION OF STANDARDIZATION AND SUPERVISION IN THE CERTIFICATION OF ESTABLISHMENT OF BUSINESS QUALIFICATION AND TAX RATES IN CONSTRUCTION SERVICES - Nevana Ayu Chumala Ningtyas; Indrawati (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The overlapping of business certification law regarding the determination of business qualifications and tax rates for Construction Services Providers by the Construction Services Development Board (referred as LPJK) as the authorized institution to issue Business Entity Certificates (known as SBU) based on the Regulation of the Minister of Public Works on Representatives of Foreign Construction Services raises disputes that inflict loss on the Construction Service Providers (Foreign) in Indonesia in terms of tax collection. The research aims to find out how the actual authority of the Construction Services Development Board regarding setting tax rates and analyze the legal protection for construction services towards differences in tax rates on construction service business certificates. The authors used a normative juridical method by collecting primary legal sources as the main basis through the statute approach, conceptual approach, and case approach. The absolute authority of issuing Business Entity Certification to determine the business classification and amount of tax in the field of construction belongs to the Construction Services Development Board as an official representative of the Directorate General of Taxes of the Republic of Indonesia. The Ministry of Public Works is only authorized to issue a power of attorney for the Construction Services to operate in all regions of Indonesia, and does not negate the absolute of the Construction Services Development Board. Discrepancies in calculating taxes cause loss to taxpayers, therefore taxpayers can file an appeal through litigation and non-litigation (mediation, conciliation, arbitration). The existence of construction services business certification is to set tax rates on construction services. The application of justice principle to the construction services certification is able to minimize disputes, both in the issuance of certificates of construction service business entities and in setting tax rates, to reach legal certainty and justice